A portable and affordable aligner for the assembly of microfluidic devices. (October 2022) - Guglielmotti, Victoria; Saffioti, Nicolás Andrés; Tohmé, Ana Laura; Gambarotta, Martín; Corthey, Gastón; Pallarola, Diego
Graphical abstract: Abstract: The incorporation of sophisticated capabilities within microfluidic devices often requires the assembly of different layers in a correct arrangement. For example, when it is desired to include electrodes inside microfluidic channels or to create 3D microfluidic structures. However, the alignment between different substrates at the microscale requires expensive equipment not available for all research groups. In this work, we present an affordable, compact and portable aligner for assembling multilayered composite microfluidic chips. The instrument is composed of aluminum machined pieces combined with precision stages and includes a digital microscope with a LED illumination system for monitoring the alignment process. An interchangeable holder was created for substrate fixing, allowing the bonding of PDMS with other materials. Microscopic visualization is achieved through any device with internet access, avoiding the need of a computer attached to the aligner. To test the performance of the aligner, the center of an indium tin oxide microelectrode on a glass substrate was aligned with the center of a microchannel in a PDMS chip. The accuracy and precision of the instrument are suited for many microfluidic applications. The small and inexpensive design of the aligner makes it a cost-effective option for small groups working in microfluidics.